2014
DOI: 10.1177/0003489414564997
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients With Abnormal Ocular/Cervical Vestibular Evoked Myogenic Potentials in the Presence of Normal Caloric Responses

Abstract: BPPV, Meniere's disease, and vestibular migraine are the most frequent diagnoses showing abnormal oVEMP and/or cVEMPs without canal paresis. Apart from these clinical entities, a portion of undiagnosed patients with multiple episodes of vertigo might have a disease that involves the otolith organs only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
(63 reference statements)
2
17
0
1
Order By: Relevance
“…The most common accompanying vestibular disorder was BPPV in this study, as also reported by other authors [1]. Utricular dysfunction has been suggested as a possible mechanism of BPPV [7]. For example, it has been reported that patients with BPPV have a tendency to show abnormal oVEMPs more frequently than cVEMPs [22].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The most common accompanying vestibular disorder was BPPV in this study, as also reported by other authors [1]. Utricular dysfunction has been suggested as a possible mechanism of BPPV [7]. For example, it has been reported that patients with BPPV have a tendency to show abnormal oVEMPs more frequently than cVEMPs [22].…”
Section: Discussionsupporting
confidence: 87%
“…The imperfect sensitivity and specificity of the caloric test can be a critical problem when defining iOD. The general definition of iOD is “abnormal function of the otolith organs despite the normal function of the semicircular canals.” In most studies reported to date, the caloric test was used as the gold standard to confirm normal function of the SCC [1-3,7,12,19]. The validity of this definition is dependent on the sensitivity and specificity of the caloric test [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caloric testing is considered as equivalent to only a low-frequency audiometric testing of the hearing [9] . Iwasaki et al [10] have reported abnormal vestibular-evoked myogenic potentials (VEMP) in some patients with BPPV having normal caloric responses. VEMP abnormality seems to be more correlated with the recurrence of symptoms in patients with BPPV [11] .…”
Section: Discussionmentioning
confidence: 99%
“…OTRAS CONDICIONES En aquellos pacientes con síntomas de vestibulopatía uni o bilateral (vértigo y ataxia) donde la exploración calórica e impulsiva es normal (15%), los VEMPs pueden resultar inequívocamente anómalos [60]. Hay sínto-mas vestibulares característicos de afectación macular, como el «drop attacks», o las sensaciones de inclinación o translación, pero en general, cuando exista desequilibrio postural, se debe pensar en afectación otolítica [61].…”
Section: Evaluación De La Función Otolítica En Niñosunclassified